2012
DOI: 10.1021/ic301682b
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Neptunium(VI) into a Uranyl Selenite

Abstract: The incorporation of neptunium(VI) into the layered uranyl selenite Cs[(UO(2))(HSeO(3))(SeO(3))] has yielded the highest level of neptunium uptake in a uranyl compound to date with an average of 12(±3)% substitution of Np(VI) for U(VI). Furthermore, this is the first case in nearly 2 decades of dedicated incorporation studies in which the oxidation state of neptunium has been determined spectroscopically in a doped uranyl compound and also the first time in which neptunium incorporation has resulted in a struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…79 Se is one of the prominent long-lived products created during the fission of actinides in nuclear reactors . The solid-state chemistry of selenium oxo-anion compounds is intricate owning to the diverse oxidation and coordination that selenium can adopt, either selenite Se IV O 3 2– or selenate Se VI O 4 2– . In the former, selenite anion SeO 3 2– possesses a stereochemically active lone pair of electrons on the Se center, which is typically three coordinated with O, forming trigonal pyramidal geometry . Examples of thorium-bearing selenite compounds for which detailed structural information is available include α-Th­(SeO 3 ) 2 , β-Th­(SeO 3 ) 2 , Th­(Se 2 O 5 ) 2 , and Th­(IO 3 ) 2 (SeO 3 ). , As the more soluble species of selenium, selenate SeO 4 2– is analogous to sulfate, and it adopts a tetrahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…79 Se is one of the prominent long-lived products created during the fission of actinides in nuclear reactors . The solid-state chemistry of selenium oxo-anion compounds is intricate owning to the diverse oxidation and coordination that selenium can adopt, either selenite Se IV O 3 2– or selenate Se VI O 4 2– . In the former, selenite anion SeO 3 2– possesses a stereochemically active lone pair of electrons on the Se center, which is typically three coordinated with O, forming trigonal pyramidal geometry . Examples of thorium-bearing selenite compounds for which detailed structural information is available include α-Th­(SeO 3 ) 2 , β-Th­(SeO 3 ) 2 , Th­(Se 2 O 5 ) 2 , and Th­(IO 3 ) 2 (SeO 3 ). , As the more soluble species of selenium, selenate SeO 4 2– is analogous to sulfate, and it adopts a tetrahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the crystal engineering of coordination polymers (CPs) has received much attention, not only because of their versatile intriguing architectures , of these compounds but also owing to their potential applications in ion exchange, catalysis, gas storage and separation, biomaterials, magnetic, nonlinear optics, , and luminescence sensors. , However, compared with the splendid works based on transition and lanthanide metals, the coordination chemistry of actinides still remains less developed. Uranium, one of the most investigated actinide elements, exhibits rich coordination chemistry, fascinating structural diversities, excellent physicochemical properties, and even the potential value in the nuclear fuel cycle. The linear uranyl (UO 2 2+ ) species, as the existing form of hexavalent uranium, in the most cases, are “off-limits” to further coordination at the axial positions. As a consequence, it only permits coordination to donors close to the equatorial plane.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Many studies have, therefore, investigated the incorporation of Np(V) into various uranyl compounds to understand the potential impact on Np(V) release, and have demonstrated that Np(V) may substitute for U(VI) based on crystallographic and chemical arguments, experiments, and computational simulations. [17][18][19][20][21][22][23][24][25][26][27][28][29] There are three major factors that may limit the incorporation of Np(V) into U(VI) compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The initial concentration of neptunium in irradiated nuclear fuel is approximately 0.5 kg per metric ton, and it increases for hundreds of years due to the decay of americium-241 ( t 1/2 = 430 years) . Under oxidizing conditions, neptunium will form the NpO 2 + (neptunyl) cation, which is soluble in water and is minimally susceptible to either hydrolysis or complexation over a wide range of conditions. Many studies have, therefore, investigated the incorporation of Np­(V) into various uranyl compounds to understand the potential impact on Np­(V) release, and have demonstrated that Np­(V) may substitute for U­(VI) based on crystallographic and chemical arguments, experiments, and computational simulations. …”
Section: Introductionmentioning
confidence: 99%